Chahar Sandough by Bahram Beyzai and Al-Malek Hova Al-Malek by Saadallah Wannous: A Comparative Study on the Function of the Protagonist’s Character - Farhad Rajabi (Tiyatro Eleştirmenliği ve Dramaturji Bölümü Dergisi)
The protagonists in Bahram Beyzai’s Chahar Sandough and Saadallah Wannous’s Al-Malek Hova Al-Malek play critical roles in the structural framework of their respective dramas. These works vividly reflect the structure of contemporary society, with the external realities influencing the protagonists and thereby enhancing their believability. The emancipatory themes, persistent interaction with individuals and society, demonstrations of power, lack of external control, and eventual triumph are key elements uniting the protagonists in these dramas. Consequently, the study identified significant parallels and shared dimensions between Baizai’s “Scarecrow” and Wannous’s “Abu Izza.” This research focuses specifically on analyzing the function of the protagonists in these two works.